A checklist of the ants (Hymenoptera: Formicidae) of Peru - Bezděčková, Klára; Bezděčka, Pavel; Machar, Ivo (Zootaxa, 2015)
The article presents a comprehensive list of the ants (Hymenoptera: Formicidae) of Peru. Distribution data for 592 valid names of species-group taxa in 76 genera and 12 subfamilies were collected through a bibliographical review. The most diverse subfamilies in terms of species richness are Myrmicinae (273 species/subspecies), Formicinae (86 species/subspecies) and Ponerinae (71 species/subspecies). The most diverse genera are Pheidole (86 species/subspecies), Camponotus (73 species/subspecies), and Pseudomyrmex (47 species/subspecies). With respect to geographic divisions, richness is highest in Madre de Dios (245 species/subspecies), followed by Huanuco (109 species/subspecies) and Cusco (104 species/subspecies). Regions in greatest need of additional survey work are Aycucho, Huancavelica, Moquegua and Tacna, from which virtually no information on the ant fauna is available.